A comparative in-vitro study of cultured primary normal human epidermal kera tinocyte on artificial dermal regeneration template and fibrin scaffold - Masri, Mohamad Fadzirul Hadzli Mohamad (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2009)
Skin plays an important role in regulating our body homeostasis. Once the dermal layer is destroyed, it cannot heal by itself, a transplant or artificial dermal regeneration template is needed in order to restore its function. This study aims to explore the successfulness in the cultivation of primary normal human epidermal keratinocyte (pNHEK) within INTEGRA® dermal regeneration template {INTEGRA ®-DRT) and fibrin. Keratinocytes were seeded on INTEGRA ®-DRT and fibrin and observed on three day basis until one week. During the culture, cells were supplied with medium containing elevated calcium in order to promote cell differentiation. The cell viability analysis, growth pattern and three dimensional views were conducted using Laser Scanning Confocal Microscope (LSCM). From the analysis, pNHEK were grown on both scaffolds and the proliferation rate was better in fibrin compared to INTEGRA ®-DRT (p < 0.05). However, the penetration rates are better in INTEGRA ®-DRT scaffold compared to fibrin. In conclusion, both scaffolds are suitable to be developed as skin substitute depends on bum situation.